(untitled) (Journal of Engineering, 2023)
Low- and medium-carbon structural steel components face random vibration and dynamic loads (like earthquakes) in many applications. Thus a modification to improve their mechanical properties, essentially damping properties, is required. The present study focuses on improving and developing these properties, significantly dampening properties, without losing the other mechanical properties. The specimens used in the present study are structural steel ribbed bar ISO 6935 subjected to heating temperatures of (850, 950, and 1050) ˚C, and cooling schemes of annealing, normalizing, sand, and quenching was selected. The damping properties of the specimens were measured experimentally with the area under the curve for the loading and unloading paths experienced from the tensile test. Considering the effect of different parameters on the damping properties, such as heat treatment temperatures, cooling rates, and carbon content, the results show that the damping properties in the annealing process at different temperatures have interesting damping properties, among other processes. Also, the highest damping energy for the annealing cooling scheme was attained at a heating temperature of 1050 ˚C, irrespective of the carbon content. Finally, better damping properties for the medium carbon content of (0.299%C) is achieved for all types of heat treatment process compared with a low carbon content of (0.188% C); and, in general, with increasing carbon content from medium to low, steel response to heat treatment increases and better damping properties are obtained.